1966
DOI: 10.1002/macp.1966.020950113
|View full text |Cite
|
Sign up to set email alerts
|

Polyacetals degradation induced by BF3‐etherates

Abstract: The degradation of polytrioxane (H, = 66,000) and copolymer of trioxane wjth 2 mole-?, of dioxolane (zn = 44,000) under the influence of BF, complexes with ðyl ether and anisole was investigated. No differences between homo-and copolymer degradations were observed. The dependence of the rate of degradation and of the molecular weight of the degraded polymer o n BF, .ether concentration was established. The expected, linear plot of the extent of degradation us. molar ratio of [BF,-etherate]/[polyacetal] i s … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

1968
1968
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…As depicted in Figure 8, the intrinsic viscosity (g) decreases when the duration of copolymerization increases, this is due probably to the reactions of intramolecular transesterification, i.e., ''back-biting,'' which causes degradation and formation of cyclic oligomers and consequently may cause a decrease of the intrinsic viscosity. The same results are obtained by Fejgin et al 54 when they polymerized TOX with DOX in the presence of BF 3 O (n-C 4 H 9 ) 2 .…”
Section: Evolution Of Intrinsic Viscosity According To Timesupporting
confidence: 87%
See 1 more Smart Citation
“…As depicted in Figure 8, the intrinsic viscosity (g) decreases when the duration of copolymerization increases, this is due probably to the reactions of intramolecular transesterification, i.e., ''back-biting,'' which causes degradation and formation of cyclic oligomers and consequently may cause a decrease of the intrinsic viscosity. The same results are obtained by Fejgin et al 54 when they polymerized TOX with DOX in the presence of BF 3 O (n-C 4 H 9 ) 2 .…”
Section: Evolution Of Intrinsic Viscosity According To Timesupporting
confidence: 87%
“…Similar results were obtained by copolymerization TOX with DOX in presence of BF 3 complex, the yield of copolymerization was reached between 65% and 77% with low molecular weight when the proportion of DOX units increases above 2.5 mol %. 54 The rate of consumption of both comonomers (TOX, DOX) is not the same, 28,55 DOX is consumed much faster and the copolymer formed initially is considerably enriched by DOX units, and an insoluble polymer is formed composed almost entirely of TOX units.…”
Section: Effect Of the Quantity Of The 13-dioxolane On The Yieldmentioning
confidence: 99%
“…In previous reports, residual catalyst or acid species from incomplete polymer purification prematurely catalyzed depolymerization of polyacetals owing to the thermodynamics of polymerization and depolymerization (Fig. 2E; see below) ( 51 ). With an improved purification method (see supplementary materials), all five polyacetal derivatives exhibited excellent thermal stability by thermogravimetric analysis (TGA), with degradation temperatures at 5% mass loss ( T d,5% ) above 337°C (fig.…”
mentioning
confidence: 87%
“…Continued addition of monomer M n increased linearly after 24 h during RD‐CROP of DXL, confirming the retention of active chain ends. In previous reports, residual catalysts or acids from incomplete polymer purification prematurely catalyzed the depolymerization of polyacetals, [161] which was improved by the authors. All polyacetal derivatives exhibited excellent thermal stability, with T d, 5% >337 °C.…”
Section: Chemically Recyclable Polyacetalsmentioning
confidence: 99%
“…In particular, the monomer recovery of PMMBL is 76%, and the residue is an oligomer that is not completely depolymerized, which makes it possible to achieve quantitative recovery of high‐purity monomers in a more effective depolymerization device. In addition, through DFT calculation, the author found that compared with PMMA, the recyclability of P(M)MBL is greatly improved not because of their different T c values, but because of the stability of linear and cyclic esters of primary and tertiary macromolecules and the differentiation of monomers [161] . Recently, Hong's group reported a series of methylene butyrolactone derived from biomass and synthesized polyacrylate polymers through efficient selective polymerization under the catalysis of Lewis acid‐base pairs.…”
Section: Chemically Recyclable Polyolefin and Polar Vinyl Monomer Pol...mentioning
confidence: 99%